Financing urban development in India - Sarma, K. S. R. N.; Indian Institute of Public Administration. Centre for Urban Studies (New Delhi : Centre for Urban Studies, Indian Institute of Public Administration, 1986)
Papers presented at a seminar organized by the Centre for Urban Studies, Indian Institute of Public Administration, 1985.
Includes bibliographical references.
Raisa
Keywords: Urbanization -- India -- Finance; City planning -- India -- Finance